Understanding Lung Cancer Resources and Barriers Among Worksites With Mostly Male Employees in Eight Rural Kentucky Counties: A Focus Group Discussion. Issue 6 (December 2019) - Knight, Jennifer Redmond; Williamson, Lucy Hollingsworth; Armstrong, Debra K.; Westbrook, Elizabeth A.
Kentucky has the highest cancer incidence and mortality rates in the United States, and lung cancer is Kentucky's leading cause of cancer deaths. Males in Kentucky have higher lung incidence and mortality rates than females. Through support from the SelfMade Health Network, Kentucky developed a Regional Resource Lead Organization that collaboratively developed a multi-component worksite intervention on lung cancer among male populations. The intervention targets eight Kentucky counties. The first component and focus of this manuscript included focus group meetings with organizational representatives in each county that provide health, educational, and social services to men and worksites. The focus groups discussed four distinct areas: (a) lung cancer-related resources and services in each county; (b) perceived ways men in worksites learn about and access health-related services; (c) identification of potential challenges and barriers to reaching men in worksites; and (d) creation of linkages and potential partnerships between community organizations and worksites. Forty-five organizational representatives participated in the eight focus groups. Most resources and services discussed were related to tobacco treatment. Employers were the most commonly perceived way men learn about and access health-related services, while attitudes and behaviors were the most commonly perceived barriers preventing men from accessing services. The most common potential linkages and partnerships across all areas were community organizations and groups, employers, health-care providers, and mass media. Partnering with employers may provide an opportunity to reach males with lung cancer prevention and control resources and services.